2015
DOI: 10.1039/c5fo00303b
|View full text |Cite
|
Sign up to set email alerts
|

Development of a low fat fresh pork sausage based on chitosan with health claims: impact on the quality, functionality and shelf-life

Abstract: A low fat fresh pork sausage based on chitosan was developed with the objective of obtaining a new functional meat product with improved properties and health claims promoting cholesterol reduction. Sausages were formulated with chitosan (2%, w/w) and different fat levels (5%, 12.5% and 20%, w/w). The results indicated that incorporation of 2% chitosan into produced pork sausages with health claims of reduction of cholesterol is technologically feasible. In addition, the chitosan reduced the microbial growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 67 publications
(172 reference statements)
7
28
0
3
Order By: Relevance
“…However, after 30 days of frozen storage, chitosan-added egg-derived yolks showed the lower TBAR values. These results are compatible with those reported by Do Amaral et al (2015) and Soultos et al (2008) that employed chitosan to reduce the lipid oxidation in meats.…”
Section: Resultssupporting
confidence: 95%
See 3 more Smart Citations
“…However, after 30 days of frozen storage, chitosan-added egg-derived yolks showed the lower TBAR values. These results are compatible with those reported by Do Amaral et al (2015) and Soultos et al (2008) that employed chitosan to reduce the lipid oxidation in meats.…”
Section: Resultssupporting
confidence: 95%
“…In other studies where chitosan was applied to different food products, this behavior was also observed. Thus, Do Amaral et al (2015) found a similar result in meat sausages after addition of 2 % (w/w) chitosan. However, Sayas- Barbera et al (2011) andSoultos et al (2008) found no significant differences between control and experimental pork hamburgers and sausages (respectively) following the addition of less than 1 % chitosan.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In this sense, SayasBarberá et al, (2011) did not found significant differences of moisture contents of fried burgers with chitosan (up to 1%) and the control. However, Do Amaral et al, (2015), who incorporated a higher chitosan percentage (1-2%) than in this study, reported a higher retention of moisture in sausages compared to the control.…”
Section: Resultsmentioning
confidence: 54%